Veganism: an extended theory of planned behavior framework incorporating ethical, environmental, and sociodemographic determinants - Öneş, Ece; Gençalp, Cansu; Avcı, Gizem; Sipahi, Simge; Kahrıman, Meryem; Yılmaz, Salim; Baş, Murat (Frontiers in Nutrition, 2026)
Background/objectivesDespite increasing global interest in veganism, integrative models that incorporate ethical, environmental, and psychosocial determinants within the Theory of Planned Behavior (TPB) remain limited in Türkiye. This study aimed to extend the TPB by including ethical, environmental, and health-related motivations to better explain individuals’ intentions and behaviors related to adopting and maintaining a vegan diet.MethodsA cross-sectional online survey was conducted among adults in Türkiye who identified with or engaged in veganism. Twelve latent variables were assessed using validated scales, and the extended model was tested through structural equation modeling with additional robustness procedures, including spline adjustments, PCA, Elastic Net regularization, and instrumental variable analyses.ResultsSubjective norms and perceived behavioral control significantly predicted vegan intention, with subjective norms emerging as the strongest determinant. Ethical motivation strongly predicted intention but did not directly predict actual adherence. Unexpectedly, environmental and health motivations were negatively associated with adherence. Women reported stronger intentions despite perceiving lower social support.ConclusionThis study broadens the TPB by integrating ethical, normative, and psychosocial dimensions that explain vegan intentions beyond traditional predictors. Findings underscore the importance of moral identity, perceived social expectations, and contextual factors in shaping sustainable dietary behaviors.